Efficacy and Safety of Non-Vitamin K Antagonist Oral Anticoagulants in Pediatric Venous Thromboembolism Treatment and Thromboprophylaxis: A Systematic Review of the Literature - Branstetter, Joshua W.; Kiskaddon, Amy L.; King, Madeleine A.; Coalter, Carli; Grubbs, Kimberly M.; Fly, Hunter; Male, Christoph; Brandão, Leonardo; Goldenberg, Neil A. (Seminars in Thrombosis and Hemostasis, 2021)
Venous thromboembolism (VTE) in children can lead to significant morbidity and mortality. Traditionally, treatment for thrombotic events in pediatric patients has been limited mainly to unfractionated heparin, low-molecular-weight heparin (LMWH), or vitamin K antagonists. Since the first non–vitamin K antagonist oral anticoagulant (NOAC) was approved for adult use, these agents have gained popularity for a variety of indications. This is largely due to their ease of administration, favorable pharmacokinetic and pharmacodynamic profile, decreased food interactions, and decreased need for therapeutic drug monitoring. Treating and preventing VTE with traditional anticoagulants in pediatric patients presents many challenges. This systematic review evaluated the current literature regarding pediatric NOAC trials. Additionally, based on an up-to-date query of clinicaltrials.gov, we detail current ongoing and as-yet unpublished clinical trials, study outcomes, and projected completion dates. Published pediatric NOAC trials have included 1,007 total children to date and have ranged from phase 1 to 4, with “indications” including both thromboembolism prophylaxis and VTE treatment. Three recent phase 3 trials, specifically involving rivaroxaban and dabigatran, have shown the agents to be at least as effective as traditional anticoagulants for acute and/or extended VTE treatment, with low frequency of recurrent thrombosis and clinically significant bleeding rates. Additionally, specially developed and tested pediatric formulations have allowed for accurate and reliable dosing, oral administration, stable pharmacokinetics and pharmacodynamics, and fewer drug or food interactions. Ongoing trials, anticipated for completion in the next few years, will reveal important information with regard to thromboembolism prophylaxis in special pediatric subpopulations and settings.
Keywords: pediatric VTE; thromboprophylaxis; NOACs